Comprehensive BCMA Expression Profiling in Adult Normal Human Brain Suggests a Low Risk of On-target Neurotoxicity in BCMA-targeting Multiple Myeloma Therapy. (April 2022) - Marella, Mathieu; Yao, Xiang; Carreira, Vinicius; Bustamante, Marta F.; Clark, H. Brent; Jackson, Carolyn C.; Zudaire, Enrique; Schecter, Jordan M.; Glover, Tynisha D.; Shenton, Jacintha; Cornax, Ingrid
B-cell maturation antigen (BCMA) is a target for the treatment of multiple myeloma with cytolytic therapies, such as chimeric antigen receptor T-cells or T-cell redirecting antibodies. To better understand the potential for "on-target/off-tumor" toxicity caused by BCMA-targeting cytolytic therapies in the brain, we investigated normal brain BCMA expression. An immunohistochemistry (IHC) assay using the E6D7B commercial monoclonal antibody was applied to 107 formalin-fixed, paraffin-embedded brain samples (cerebrum, basal ganglia, cerebellum, brainstem; 63 unique donors). Although immunoreactivity was observed in a small number of neurons in brain regions including the striatum, thalamus, midbrain, and medulla, this immunoreactivity was considered nonspecific and not reflective of BCMA expression because it was distinct from the membranous and Golgi-like pattern seen in positive control samples, was not replicated when a different IHC antibody (D6 clone) was used, and was not corroborated by in situ hybridization data. Analysis of RNA-sequencing data from 478 donors in the GTEx and Allen BrainSpan databases demonstrated low levels of BCMA RNA expression in the striatum of young donors with levels becoming negligible beyond 30 years of age. We concluded that BCMA protein is not present in normal adult human brain, and therefore on-target toxicity in the brain is unlikely.